Future agriculture and food supply chain - not even doomsday preppers got it right - Filip Stefanic; Ivan Stefanic (Ecocycles, 2017)
Future agriculture and food supply chain is one of the pillars of human survival and prosperity in the long run. The planet’s ecosystem is very fragile and influenced by a large array of very diverse natural and human factors which are frequently interdependent. Regardless of root cause, climate change, pollution and depletion of non-renewable resources and several other unfavorable processes are in place. We can argue that the increase of the average temperature is just a part of a long-term natural cycle and not the consequence of human negligence and pollution, but in the end, it doesn’t matter. The ecosystem is changed and agricultural plants might not survive the change and adopt in time. Relevant and fairly reliable indicators are available, but it seems that nobody is paying attention to those staggering numbers and trends. Doomsday preppers are well known to be a rather suspicious and concerned group of people about the reliability of future food supply chain. But even they somehow assume that agricultural production will go on, and the only problems that could occur are short run disruptions in distribution.